Análisis de vibración como método de diagnóstico para cambiadores de tomas en carga - Rivas Trujillo, Edwin; Burgos, Juan Carlos; García, Juan Carlos (Ingeniería, 2007)
The suitable condition of an On-load Tap of a power transformer. There are a variety of OLTC diagnosis techniques, some of them can be used only off-line and some of them can be used on-line. This paper describes some of the methods used for the diagnosis of power transformers OLTC and emphasizes the vibration analysis as a tool of OLTC condition assessment. The main OLTC vibration parameters are obtained using envelope analysis based on Hilbert transform as the pre-processing of wavelet decomposition. Previously normalized and synchronize signals. To validate the method was compared the signal vibration under normal conditions and failures realistic implemented laboratory.